PENERAPAN TEORI KONSTRUKTIVISME UNTUK SOLUSI KRISIS LITERASI MEMBACA INDONESIA - Dewi Nur Halimah; M Mamduh Winangun (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Indonesia's education system faces a severe reading literacy crisis according to the PISA 2022 OECD report. The national score is only 359 points, down from 371 points in 2018. 75% of students fall below Level 2 minimum competency. National media Detik.com reports concerns from the Ministry of Education staff that Indonesia risks falling behind ASEAN countries like Vietnam. This literature review analyzes Piaget and Vygotsky's constructivism theory as a systemic solution. Findings demonstrate the effectiveness of Zone of Proximal Development (ZPD), scaffolding, as well as literature circles and inquiry reading strategies. A Lesson Plan (RPP) for the Merdeka Curriculum is developed with potential to improve PISA scores by 25 points based on Hattie's meta-analysis (Detik Edu, 2025; IRJE, 2024).